2013
DOI: 10.1590/s2236-89062013000300005
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura e composição florística de um Cerrado sensu stricto e sua importância para propostas de restauração ecológica

Abstract: -(Structure and floristic composition of a Cerrado sensu stricto and its relevance to ecological restauration). Edges are transition areas between two adjacent ecosystems that can be originated by natural or anthropogenic events. The edge influence includes both direct effects, related to changes on microenvironmental factors, as well as indirect effects, related to changes in species interactions. Additionally, some studies suggest that microenvironmental factors are altered by the cardinal orientation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 51 publications
1
44
0
6
Order By: Relevance
“…The absolute density was 15 278 individual trees per hectare, with a basal area (area occupied by the cross-section of the tree's trunk at breast height) of 27.75 m 2 ha -1 and Shannon diversity index of 4.03 in our study area, which are similar to values found in other Cerrado areas (Reys, 2008). According to Reys et al (2013) the main vegetation species found in the study area are: Vochysia tucanorum; Miconia rubiginosa; Pterodon pubescens; Ocotea pulchella; Xylopia aromatica; Copaifera langsdorfii; Myrcia splendens; Bauhinia rufa; Virola sebifera; and Myrcia guianensis. Details about the phenology of the study area can be found in Reys (2008) and Reys et al (2013).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute density was 15 278 individual trees per hectare, with a basal area (area occupied by the cross-section of the tree's trunk at breast height) of 27.75 m 2 ha -1 and Shannon diversity index of 4.03 in our study area, which are similar to values found in other Cerrado areas (Reys, 2008). According to Reys et al (2013) the main vegetation species found in the study area are: Vochysia tucanorum; Miconia rubiginosa; Pterodon pubescens; Ocotea pulchella; Xylopia aromatica; Copaifera langsdorfii; Myrcia splendens; Bauhinia rufa; Virola sebifera; and Myrcia guianensis. Details about the phenology of the study area can be found in Reys (2008) and Reys et al (2013).…”
Section: Study Areamentioning
confidence: 99%
“…According to Reys et al (2013) the main vegetation species found in the study area are: Vochysia tucanorum; Miconia rubiginosa; Pterodon pubescens; Ocotea pulchella; Xylopia aromatica; Copaifera langsdorfii; Myrcia splendens; Bauhinia rufa; Virola sebifera; and Myrcia guianensis. Details about the phenology of the study area can be found in Reys (2008) and Reys et al (2013).…”
Section: Study Areamentioning
confidence: 99%
“…This vegetation grows on an oxisol, which is sandy, acidic (pH < 4.0), low in availability of macronutrients and high in exchangeable Al (Reys et al 2013). The climate in this region is classified as Cwa (Köppen 1948) with wet summer and dry winter.…”
Section: Study Site and Species Selectionmentioning
confidence: 99%
“…The device was designed to be easily transported and installed in the field, more specifically in a 300-ha wooded Cerrado area (a tropical woodland) located in the municipality of Itirapina, São Paulo state, Brazil (latitude 22°10′ S, longitude 47°52′ W; Figure 1). The vegetation density in this undisturbed forest is estimated as 15,522 individuals per hectare, and the largest trunk diameter and highest canopy found were 34.7 cm and 12 m, respectively (Reys et al, 2013). The climate classification for this area is Cwa subtropical characterized as hot and rainy summer (October to March) and dry winter (April to September) according to the Köppen climate classification.…”
Section: Study Areamentioning
confidence: 91%